Spontaneous expulsion of a huge cervical leiomyoma from the vagina after cesarean: A case report with literature review. Issue 33 (August 2018) - Zhang, Jian; Zou, Bingyu; Wang, Kana
Abstract: Rationale: As more and more women delay their child bearing age, the prevalence of uterine fibroids during pregnancy is likely to increase. Patient Concerns & Lessons: We report a Chinese Tibetan case with spontaneous expulsion of a huge cervical myoma after cesarean. Decreased blood supply of the myoma and the uterine contraction may contribute to the spontaneous expulsion. Vaginal-myomectomy is recommended as the initial treatment.